IMPROVEMENT OF THE MANAGEMENT SYSTEM OF THE EURO-ASIAN INTEGRATION OF THE REGION IN WORLD TRANSPORT (British Journal of Global Ecology and Sustainable Development, 2023)
The article considers and analyzes the values and mechanisms of the foreign economic integration of the countries of the Eurasian region in world transport in modern conditions. It reveals the essence of the logistic integration of regions at the macro and meso-economic levels in the system of world economic relations. The article also discusses the measures taken by the SCO member states to create new and modernize existing road and rail routes on their own territories and on the territory of neighboring CIS states. In conclusion, it indicates that positive developments in the development of the transport sector will largely depend on the ability of its participants to develop a coordinated policy in the transport and logistics sector.